Influence of Rivalry Merger, Bank Financial Health Rating, and Customer Loyalty to the Competitive Advantage - Fajar Kurniawan; Erie Febrian; Angki Wibisono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The growth of the sharia banking market in Indonesia tended to stagnate. The Government had taken initiative to strengthen the sharia banking market by merging the three state sharia banks. PT. Bank Muamalat Indonesia, Tbk. (BMI), which is categorized in one of strategic group, is expected to be affected by considering that both BMI and the three state sharia banks have alike market segment. BMI is known as the first and purely sharia bank, which owns strong customer base. Thus, in last few years it is always the champion in term of customer loyalty among the public sharia banks. Internally, BMI attempts to strengthen its capital as one of indicator in bank financial health rating. The research objective is to analyse the influence of rivalry merger, bank financial health rating, and customer loyalty to the competitive advantage of BMI. The research utilizes quantitative method to test the hypothesis by using Partial Least Square (PLS). The result of data analysis from the survey shows that there is significant influence of rivalry merger, bank financial health rating, and customer loyalty to the competitive advantage.